Creativity - Parish, Steve, 1945-; Prentice, Kate (Glebe, NSW : Pascal Press, 2013)
The series of books offer insights into creating a rich and fulfilling life connected to soul and nature. There is no handbook to life given to us when we enter this world. We are born into a diversity of life situations which we will accept or deny: growing and learning, adapting and searching, each of us finding a path.
Keywords: Nature -- Pictorial works; Self-actualization (Psychology); Australian; Photobooks